2019
DOI: 10.1002/batt.201900051
|View full text |Cite
|
Sign up to set email alerts
|

Stable Acetals of Glyoxal as Electrolyte Solvents for Lithium‐Ion Batteries

Abstract: In this manuscript, we report for the first time about the use of the glyoxylic‐acetals‐based electrolytes in combination with graphite electrodes. We showed that these innovative electrolytes display good viscosities and conductivities, as well as higher thermal stability and flash points compared to the electrolyte based on conventional solvents. Additionally, they display intrinsic film‐forming ability and they can be successfully used in combination with graphite electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…As already reported by Heß et al, the assumed SEI film forming ability of TME and TEE should be included in the consideration. 29 Figure 2 shows the electrochemical response of different solvent ratios of TME:PC (1:x 2 w/w, x 2 = 6, 4, 2, 1.4) in graphite||Li cells. Compositions of 1:6 w/w (TME:PC) and lower lead to PC-exfoliation in the first cycle (see inset Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As already reported by Heß et al, the assumed SEI film forming ability of TME and TEE should be included in the consideration. 29 Figure 2 shows the electrochemical response of different solvent ratios of TME:PC (1:x 2 w/w, x 2 = 6, 4, 2, 1.4) in graphite||Li cells. Compositions of 1:6 w/w (TME:PC) and lower lead to PC-exfoliation in the first cycle (see inset Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They are also promising solvents for electrochemical double-layer capacitors. 28,29 Equally, the solvents are cheap, abundant and easy to synthesize at large scale. 28 However, the low relative permittivity, resulting in a low ionic conductivity has to be improved.…”
mentioning
confidence: 99%
“…Nonetheless, as already reported, the transport properties of the two glyoxal electrolytes are suitable for their use in LIBs, and both guarantee good performance in a broad range of C‐rates [17b,e] . Not to forget that electrolytes based on TEG display higher thermal stability, lower vapor pressure, and higher boiling points compared to LP30 [17b,d] …”
Section: Resultsmentioning
confidence: 62%
“…As discussed in the introduction, the poor stability showed by graphite electrodes when used in combination with etherbased electrolytes represents one of the limitations associated to the use DOL in LIBs [8,16] and low concentration (1 M) electrolyte is reported to provide limited protection on graphite electrodes. [17] On the other hand, it has been shown that graphite alloy and conversion electrodes are working very well in combination with TEG-based electrolytes [18] as they are able to form a stable and homogenous SEI. [19] Figure 2a shows the charge-discharge profile at 0.1 C of graphite cycled in combination with DT2F.…”
Section: Resultsmentioning
confidence: 99%